Evaluation of options portfolios for exchange rate hedges - Miguel Jiménez-Gómez; Natalia Acevedo-Prins; Miguel Rojas-López (Institute of Advanced Engineering and Science, 2021)
In this paper evaluate six exchange rate hedging strategies with financial options from the OTC market in Colombia. Three hedging strategies for importers and three for exporters were raised. The coverage for importers was carried out with the traditional strategy of long call, bull call spread and bull put spread, the last two correspond to options portfolios. the coverage for importers was carried out with the traditional strategy of long put, bear call spread and bear put spread, the last two correspond to options portfolios. to determine the best hedging strategy, the currency price was modeled with a Wiener process and the VaR for the six covered scenarios was calculated and compared with the VaR of the uncovered scenario. The results shown by the six hedging strategies manage to mitigate the exchange risk, but the most efficient strategies are the traditional ones for both importers and exporters.